Belonging and unbelonging in Fatou Diome's The belly of the Atlantic. (1st September 2016) - Latha, Rizwana Habib
ABSTRACT: This article explores the issue of belonging and unbelonging in The belly of the Atlantic by Fatou Diome. The central factor of reflexivity in the novel is underscored by the elements of positionality, auto-ethnography and intertextuality that promote representations of the self, as well as of local and global socio-political and religious concerns. In this semi-autobiographical narrative, Salie, the protagonist, is portrayed as a migrant writer whose multifaceted identity promotes significant insights into the underbelly of migrant experiences and the split subjectivities of African migrants in Europe. The complex dialogues that result from intertextuality emerge both explicitly and implicitly in significant areas of The belly of the Atlantic, thereby establishing links with writers in local and global places. The intertwining of fact and fiction in this third-generation Senegalese novel evokes a journey from roots to routes through transnational linguistic hybridity and the interweaving of genres. Although Salie's positionality is shaped by her challenging movements between local and global spaces and places, this fluidity promotes her agency and articulation as an individual, and has the effect of intensifying creativity and self-reflexivity. However, the multiple possibilities of gender activism are not fully explored within the ambit of the human rights agenda in the novel, and the protagonist's feelings of belonging and unbelonging lead to ambivalence in her representation of Muslim identities in a traditional African context. As the novel has been positively received globally, this factor raises the strong possibility of essentialism in readers' responses to the cultural and religious identities represented in this text.